Sustaining the Quality of Sports Participation and Life Standards in Aging Men: A Systematic Review of Physical Activity and Urological Health Management - Studziński, Dawid; Szkatuła, Wiktoria; Osińska, Karolina; Kołcz, Anna; Kulczak, Michał; Turczynowski, Konrad; Turczynowski, Kamil; Trzepizur, Alicja; Pietrucha, Jakub; Ochońska, Izabela (Quality in Sport, 2026)
This systematic review formulates an organizational service framework integrating clinical urological data with sports management practices to mitigate disease-induced dropout among aging male athletes. Following PRISMA guidelines, a systematic search of PubMed (2021–2026) yielded 22 primary open-access articles evaluating physical activity, sedentary behaviors, and male urological or renal outcomes. High-volume cohort data confirms a robust inverse relationship between regular physical activity and the severity of lower urinary tract symptoms and erectile dysfunction, though extreme training volumes display a non-linear risk threshold. In clinical rehabilitation phases, supervised technological exercises paired with behavioral compliance models significantly accelerate post-surgical continence recovery. Longitudinally, overactive bladder symptoms serve as independent predictors of upper-limb grip strength decline and physical frailty. Sports enterprises can optimize service quality and member retention by moving from generic configurations toward age-appropriate, urologically sustainable exercise designs. Practical administrative interventions include expanding facility restroom accessibility to reduce public anxiety and embedding non-invasive urological screening metrics into routine physical assessments to preserve lifelong functional longevity.